2019
DOI: 10.1073/pnas.1903126116
|View full text |Cite
|
Sign up to set email alerts
|

Despite high objective numeracy, lower numeric confidence relates to worse financial and medical outcomes

Abstract: People often laugh about being “no good at math.” Unrecognized, however, is that about one-third of American adults are likely too innumerate to operate effectively in financial and health environments. Two numeric competencies conceivably matter—objective numeracy (ability to “run the numbers” correctly; like literacy but with numbers) and numeric self-efficacy (confidence that provides engagement and persistence in numeric tasks). We reasoned, however, that attaining objective numeracy’s benefits should depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
4
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 73 publications
(83 reference statements)
2
68
4
6
Order By: Relevance
“…Although the best combination of subjective and objective financial knowledge is to have corresponding high levels on both, our results also indicate that subjective financial knowledge in itself is beneficial for financial outcomes. Thus, our results are not consistent with studies suggesting that the benefits from having high confidence accrue only on individuals with adequate competences (Peters et al 2019). Further research is needed on when overconfidence is beneficial/harmful for financial behavior, and which underlying psychological mechanisms can help to explain why.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although the best combination of subjective and objective financial knowledge is to have corresponding high levels on both, our results also indicate that subjective financial knowledge in itself is beneficial for financial outcomes. Thus, our results are not consistent with studies suggesting that the benefits from having high confidence accrue only on individuals with adequate competences (Peters et al 2019). Further research is needed on when overconfidence is beneficial/harmful for financial behavior, and which underlying psychological mechanisms can help to explain why.…”
Section: Discussioncontrasting
confidence: 99%
“…Underconfidence may also influence financial behavior negatively if, for example, individuals become increasingly reluctant to make necessary active financial choices. Peters et al (2019) showed that people who exhibit "mismatched" levels of objective and subjective numeric ability self-report worse financial and medical outcomes. In addition to confidence, it is therefore important to assess the link between under-and overconfidence and financial behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Such efforts may be particularly important to health when good outcomes depend on numeric ability but also persistence over time. 46 The current findings imply a multifaceted nature of numerical competencies underlying risk comprehension. Subjective numeracy scales have often been used as a proxy for actual numerical abilities, 11,14 despite offering a poor diagnostic tool for assessing objective numeracy.…”
Section: Discussionmentioning
confidence: 62%
“…Such efforts may be particularly important to health when good outcomes depend on numeric ability but also persistence over time. 46…”
Section: Discussionmentioning
confidence: 99%
“…Living in today's society requires well-developed mathematical competencies. As more cliché as this statement may sound, there is a robust scientific literature indicating that higher mathematical competencies are associated with higher employability and incomes [1][2][3], profitable financial decisions [4], and even better health outcomes [5]. Despite this well-established body of evidence, many adults and children, even from developed countries, struggle to perform simple arithmetic [6].…”
Section: Introductionmentioning
confidence: 99%